Cargo Transportation Adriatic- Danube Region with Reference to Croatian Harbours and Ports - Jurum Kipke, Jasna; Štrumberger, Nada; Kovačević, Dražen (Promet - Traffic&Transportation, 2012)
The paper considers the role of the Croatian sea harbours,the Croatian ports, 1iver navigation and wateiWays dependingon the transport routes between the Adriatic and the Danuberegion.The strategic and economic position best describes the roleof the economic bridge spanning the N01th and the South,whether speaking of the Adriatic corrid01; which has harbourswith all kinds of technologies, or of the combined transportAdriatic - Danube-region co1Tidor, and our river ports.Conside1ing the difficulties cwTently present due to the wardestruction, which have disturbed the technological processesat our harbours and ports, as well as the Adriatic - Danube-region commodity trade, we have to continue investing allour efforts in order to prevent our harbours and p01ts of beinglimiting factors of cargo flows between the Adriatic and theDanube-region.Taking into account the transportation flows towards theCentral European countries, our duty is to create modem andcompetitive traffic and thus emphasise our role on the Europeanand world market.